Is Hypoalbuminemia a Predictor for Acute Kidney Injury after Coronary Bypass Grafting in Diabetes Mellitus Patients? - KÖKSAL, CENGİZ; Aksoy, Rezan; Adademir, Taylan; Yilmaz, Ekrem; Cevirme, Deniz; Sengor, Mehmet; KÖKSAL, CENGİZ; Rabus, Murat Bulent (My University, 2019)
Objective: Acute kidney injury (AKI) is one of the most important complications after coronary artery bypass grafting (CABG) procedure. Serum albumin, which is an acute phase reactant, is suggested to be associated with AKI development subsequent to various surgical procedures. In this study, we research the relation between preoperative serum albumin levels and postoperative AKI development in diabetes mellitus (DM) patients undergoing isolated CABG.